61 AUDIT: MEDICATION REVIEW POST INPATIENT FALLS. (18th November 2021) - Gibbons, C; Gaynor, E; Duggan, J; Blackstock, J; Mullen, M; Keena, A; Buckley, R; Callaly, E
Abstract: Background: Falls are the most commonly reported incident in the Health Service Executive (HSE). Inappropriate medications and polypharmacy in the elderly can contribute to increased falls risk. Our aim was to assess whether a medication review was being completed at the time of the post-fall clinician review. Methods: We completed a retrospective chart review using an audit tool of consecutive inpatient falls, resulting in serious injury, from March–December 2019. Standards measured against were: HSE Guideline—Service User Falls: A Practical Guide for Review, Medicines and Falls in Hospital: British Society Guidelines, STOPP & START criteria and NICE Guidelines: Falls in Older People 2013. Results: We identified 33 charts for review (n = 33)—54.55% (18) female and 45.45% (15) male. Average age was 81 ± 11.2 years. The immediate post-fall review was mainly completed by interns (48.49% (16)) and SHO's (39.39% (13)). A medication review was carried out 9.09% (3) of the time. A total of n = 28 (84.85%) had poly pharmacy. When analysed for medications known to increase risk of falling, 51.52% (n = 17) were on anti-hypertensives, 45.45% (n = 15) on laxatives, 24.24% (n = 8) on sedative medications, 18.18% (n = 6) on hypnotics/anxiolytics, 15.15% (n = 5) on opioids and 15.15% (n = 5) on diuretics at the time of fall. The majority of these medications (77.42% (n = 24)) were commenced prior to admission. None of these medications were discontinued or the dose changed on review post fall. Conclusion: Our audit demonstrates that in a cohort of patients who had an inpatient fall medication discontinuation and dose reductions were not performed. Yet, a high burden of polypharmacy and high-risk falls medication were found. This may result in missing a pertinent opportunity to prevent future falls. We advise a structured medication review is carried out for each patient who suffers an in-patient fall to efficiently modify such an easily identifiable risk factor.